A empatia em acadêmicos de medicina em relação ao paciente pediátrico: Estudo transversal unicêntrico, 2019 - Cosmo, Naira Silva (2019)
Introduction: Empathy involves the ability to identify and perceive the patient's personal feelings and experiences, as well as the ability to see the world from another person's perspective. In Pediatrics, there is the challenge of looking for a good relationship with the patient and their caregivers, which are fundamental pieces of care and treatment performance. Objective: To evaluate the level of empathy of medical students in relation to pediatric patients. Materials and methods: Cross-sectional study conducted with students from 4th and 6th year of medical school at UNIFENAS - Alfenas. Empathy levels were assessed using the Jefferson Empathy Scale. A sociodemographic questionnaire collected data on possible independent variables such as gender, age, marital status, children, previous degree, having siblings, chronic personal and familiar diseases, mental disorders, intended medical specialty, among others. Descriptive analysis was performed using mean and standard deviation for continuous variables and frequency distribution for categorical variables. Student’s T test was performed to compare empathy score and categorical variables and the two-tailed Fischer exact test to compare categorical variables. Variables with p≤0.25 were analyzed by multiple regression analysis. The level of significance was 0.05. Results: 159 students participated in the research, but 10 were eliminated due to incomplete fill of the questionnaires. Final sample had 149 students, 74 from 4th year and 75 from 6th year. There was no difference between the overall empathy score between 4th and 6th years students, even though both had high overall levels of empathy, except for the Ability to Stand in the Patient’s Shoes domain. The overall empathy score was higher in females (padjusted = 0.011), as was the compassionate care domain score (padjusted = 0.013). Volunteers reporting chronic familiar disease and those who had difficulty performing a pediatric physical examination had a significantly higher score in the Compassionate Care domain (padjusted = 0.038 and padjusted = 0.037, respectively). Conclusion: the global empathy score and its different domains were high, except for the Ability to Stand in the Patient’s Shoes domain. There was no relationship between empathy and its different domains and the year of the medical course. Women had higher levels in the global score and in the Compassionate Care domain. Students with a chronic familiar illness and difficulty in performing the pediatric physical examination also had a higher Compassionate Care score